A porphyrin cobalt(ii) complex linked to a TiO2/BiVO4 nanocomposite: alcohol oxidation using nanohybrid materials as a photocatalyst via a mechanism approach. (5th January 2018) - Askari, Parvin; Mohebbi, Sajjad
Abstract : A novel visible light-sensitized nanohybrid, Co–TCPP@TiO2 /BiVO4, was used as a highly efficient, stable, reusable, and robust photocatalyst using O2 towards aldehyde production. Abstract : Herein, a new nanohybrid catalyst was synthesized via covalently linking a tetraacetate porphyrin cobalt(ii ) complex to a TiO2 /BiVO4 nanocomposite, and its photocatalytic efficiency towards alcohol oxidation under visible light irradiation was monitored by GC. This nanohybrid material was implemented as a photocatalyst and characterized by the following physicochemical techniques: FE-SEM imaging, EDS, XRD, DRS, BET analysis, and FTIR spectroscopy. Additionally, its role as a photocatalyst was evaluated using a mechanistic approach under aerobic conditions by changing several parameters such as solvent, substrate, oxidant, amount of catalyst, reaction temperature, and ratio of oxidant to substrate. The photocatalytic activity of this nanohybrid catalyst, with an average size of 24 nm, increased almost twice as compared to that of the TiO2 /BiVO4 nanocomposite from 35% to 85% conversion, whereas the selectivity was 99%. A plausible mechanism was proposed. In fact, the cobalt porphyrin complex as a light sensitizer improves the photocatalytic activity through impregnation onto the TiO2 surface. The photocatalyst was reused several times without significant loss of its activity. Thus, this nanohybrid robust catalyst has excellent advantages such as facile synthesis, high activity and selectivity, and use of O2 and other environmentally friendly oxidants under mild conditions towards aldehyde production.